ANALISIS PENGARUH SISTEM INFORMASI MANAJEMEN (SIM) DAN KOMPETENSI PEGAWAI TERHADAP KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN BANDUNG - Yunny Yuniarty (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The Population Administration Information System is regulated by the Minister of Home Affairs Regulation 95 of 2019 concerning the Population Administration Information System in terms of providing services to the community is not optimal, this is because population data that was originally manual became online. The research method used by the researcher is to use quantitative methods. The sampling technique used is census (saturated sampling). The data procedure carried out was observation, interviews, and questionnaire dissemination. While the research analysis uses Multiple Linear Regression Analysis, but before multiple regression analysis, the existing data is still in the form of ordinal data that must be validated first with the consecutive interval (MSI) method. Based on the results of the research conducted by the author on the Influence of SIM and Employee Competencies on Service Quality at the Bandung Regency Population and Civil Registration Office, the author can conclude that the management information system and employee competencies that affect the quality of service at the Population and Civil Registration Office have not fully achieved optimal results. Management information system variables and employee competencies have a significant influence on service quality. With that, it can be said that Ho is rejected and Ha is accepted, meaning that the hypothesis is proven to be correct that: The variables of management information system (X1) and employee competence (X2) have a positive and significant influence on the variable of service quality (Y). Therefore, the hypothesis proposed by the author is acceptable.